Polyarginine Decorated Polydopamine Nanoparticles With Antimicrobial Properties for Functionalization of Hydrogels - Muller, Céline; Berber, Emine; Lutzweiler, Gaetan; Ersen, Ovidiu; Bahri, Mounib; Lavalle, Philippe; Ball, Vincent; Vrana, Nihal E.; Barthes, Julien (Frontiers in Bioengineering and Biotechnology, 2020)
Polydopamine (PDA) nanoparticles are versatile structures that can be stabilized with proteins. In this study, we have demonstrated the feasibility of developping PDA/polypeptides complexe in the shape of nanoparticles. The polypeptide can also render the nanoparticle functional. Herein, we have developed antimicrobial nanoparticles with a narrow size distribution by decorating the polydopamine particles with a chain-length controlled antimicrobial agent Polyarginine (PAR). The obtained particles were 3.9 ± 1.7 nm in diameter and were not cytotoxic at 1:20 dilution and above. PAR-decorated nanoparticles have exhibited a strong antimicrobial activity against S. aureus, one of the most common pathogen involved in implant infections. The minimum inhibitory concentration is 5 times less than the cytotoxicity levels. Then, PAR-decorated nanoparticles have been incorporated into gelatin hydrogels used as a model of tissue engineering scaffolds. These Nanoparticles have given hydrogels strong antimicrobial properties without affecting their stability and biocompatibility while improving their mechanical properties (modulus of increased storage). Decorated polydopamine nanoparticles can be a versatile tool for the functionalization of hydrogels in regenerative medicine applications by providing bioactive properties.